Sex differences in extinction to negative stimuli: Event-related brain potentials - Sun, Nan (Medicine (Baltimore), 2018)
There are controversial observations regarding whether females have a longer time to extinction than men, which may be related to different levels of conditioning acquisition and/or the influence of the menstrual cycle. We explored the electrophysiological evidence of sex differences in extinction. In this study, females in the luteal phase and menstrual phase were examined for event-related potential (ERP) and evidence of attention allocation in the conditioning model using electroencephalogram recordings. A group of male participants was also included and compared. Women in the luteal phase had a higher difference waveform of P3 amplitude to conditioned stimulus (CS) in the extinction phase than women in the menstrual phase and men. There was a shorter latency of P3 to CS+ in men than in women in the extinction phase, suggesting that men react faster than women to unconditioned stimulus (US) expectation. Our study revealed that women in the luteal phase allocated more attentive resources to the expectation of a US. In contrast, men displayed faster expectation of the extinguished US than women. Our results support the superiority of ERP technology in documenting the neural mechanism of the extinction process.